2018
DOI: 10.1111/jcmm.13983
|View full text |Cite
|
Sign up to set email alerts
|

Exploring macrophage cell therapy on Diabetic Kidney Disease

Abstract: Alternatively activated macrophages (M2) have regenerative properties and shown promise as cell therapy in chronic kidney disease. However, M2 plasticity is one of the major hurdles to overcome. Our previous studies showed that genetically modified macrophages stabilized by neutrophil gelatinase‐associated lipocalin (NGAL) were able to preserve their M2 phenotype. Nowadays, little is known about M2 macrophage effects in diabetic kidney disease (DKD). The aim of the study was to investigate the therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Similar to this study, it has been found that NGAL KO mice had worse renal damage after IR-induced AKI [86]. Furthermore, NGAL therapy is effective in DN [87]. In this study, macrophage NGAL cell therapy increased the anti-inflammatory molecule IL-10 and decreased the proinflammatory molecule TNF-α, indicating that NGAL overexpressing macrophage therapy could reduce inflammation in DN.…”
Section: Macrophages Phenotype Under the Control Of Bioactive Moleculsupporting
confidence: 85%
“…Similar to this study, it has been found that NGAL KO mice had worse renal damage after IR-induced AKI [86]. Furthermore, NGAL therapy is effective in DN [87]. In this study, macrophage NGAL cell therapy increased the anti-inflammatory molecule IL-10 and decreased the proinflammatory molecule TNF-α, indicating that NGAL overexpressing macrophage therapy could reduce inflammation in DN.…”
Section: Macrophages Phenotype Under the Control Of Bioactive Moleculsupporting
confidence: 85%
“…Previous studies also have confirmed that the phagocytic activity of M2 Mφ is more efficient than that of M1 cells. 52,53 They attributed this to the higher activity of M2 Mφ in scavenging debris and tissue remodeling. 54,55 Furthermore, following hypoxia incubation of RAW264.7 cells for 24 h, CLU expression was enhanced (Figure 3), but those of the M1 marker CD80 and the M2 marker CD206 decreased, while the phagocytosis was also increased (data not shown).…”
Section: Clu Is Associated With Decreased Polarization To M1 After LImentioning
confidence: 99%
“…We already demonstrated that cell therapy with modified macrophages ameliorate kidney damage in different experimental renal pathologies by decreasing the inflammatory scenario 5 7 . Given the properties of Ivns1abp-macrophages in actin cytoskeleton stability and the resistance against inflammatory insults, we therefore investigated whether cell therapy with these modified macrophages preserve kidney function and epithelial integrity against the inflammatory damage associated with I/R injury.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, given the properties of macrophages overexpressing Ivns1abp in actin cytoskeleton stability and resistance to inflammation and following our previous experience in cellular therapy with macrophages in renal pathology 5 7 , we hypothesized that these macrophages could be used as a treatment for damage associated with I/R injury. The experiments revealed that BMDMs that overexpress Ivns1abp were highly protective of renal function as well as the epithelial structure of renal tubules preventing mismatches of actin cytoskeleton loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation